Pembuatan pupuk organik dengan agensi hayati untuk meningkatkan nilai tambah ekonomi aktivitas proklim Desa Wonocoyo Trenggalek - Ernoiz Antriyandarti; Ihsannudin Ihsannudin; Eka Handayanta; Suko Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
As a village that received an award from the Climate Village Program (Proklim) and towards ‘proklim lestari’ from the Ministry of Environment and Forestry (LHK), Wonocoyo has managed household waste and cow dung waste into liquid and solid organic fertilizer, but these products do not have advantages. Therefore, community empowerment is carried out by improving the quality of the organic fertilizer with biological agents. This community empowerment activity aims to increase the economic added value of the Proklim activities of Wonocoyo Village through the manufacture of organic fertilizers with biological agents and commercialize it. This activity applied the Participatory Action Research (PAR) method by using extension, training, technical guidance and facilitating marketing. The results of the activity show that the use of biological agents can improve the quality as well as the economic added value of organic fertilizer produced by Wonocoyo Village, which has been able to process organic waste into organic fertilizers with a production capacity of 500 kg/month. This activity is aimed at Sustainable Agriculture or the Green Economy, in accordance with the 2nd goal of the Sustainable Development Goals (SDGs).